Sikap Keuangan,Lingkungan Kampus Dan Literasi Keuangan Terhadap Manajemen Keuangan Pribadi Mahasiswa - Hartiningsih Astuti; Moehadi Moehadi; Dimas Surya Atmaja; Siti Ayu Ulandari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The aim of this research is to find out how students' personal financial management is influenced by financial attitudes, university environment, and financial literacy. To achieve financial security in the future, students must practice effective money management. When assessing and responding to financial management techniques, a person's psychological tendencies are reflected in their financial outlook. Financial management practices among students are also influenced by the intellectual, social and physical components of campus life. Having a solid understanding of finances allows a person to make informed judgments about money. This research analyzes data collected from Bojonegoro University students using multiple linear regression techniques. Research findings show that although financial literacy has different influences, financial attitudes and the campus environment have a large influence on students' personal financial management. These results provide important information to academic institutions and other relevant stakeholders to create policies and initiatives that aid the acquisition of money management skills by students. It is believed this research will help students become more financially secure and better prepared to face financial difficulties in the future.